Factors Influence Corporate Social Responsibility Disclosure - Wike Mardiana; Anik Irawati (Faculty of Economic and Business, 2019)
This study aims to analyze factors influence Corporate Social Responsibility Disclosure in palm oil plantation companies in Indonesia and Malaysia. This study analyzes influences of total assets, profitability, leverage, independent proportion of commissioners, the proportion of independent audit committee. This study is conduct on financial reports published in Indonesia and Malaysia. Methods of data collection are taken from the annual financial statements in Indonesia Stock Exchange of 17 companies and Bursa Malaysia of 22 companies. Data analysis techniques used multiple regressions. The results showed that; 1) there is no influence of total asset, profitability, leverage, and proportion of independent audit committee in palm oil plantation companies in Indonesia and Malaysia; 2) there is influence of independent board of commissioner on CSR disclosure practices in palm oil plantation companies Indonesia and Malaysia